Bleeding feature in the Hematology department in Brazzaville, Congo - Felix Malanda, Irene Ondzoto Ibata, Alexis Elira Dokekias, Lydie Ocini Ngolet, Jennie DorothÃƒÂ©e Ok (Journal of Medical Biomedical and Applied Sciences, 2017)
Background: Epidemiological and clinical characteristics data of patients with bleeding symptoms are unknown.Methods: a total of 6961 medical records of patients admitted in the hematology department in a teaching hospital from 2000 to 2016 were reviewed. We enrolled in the study all patientsâ medical records that were reporting bleeding complications and analyzed retrospectively their epidemiological data, severity, clinical and biological characteristics.Results: A total of 35 people (20 men and 15 women), with a median age of 29 (range 3 and 76) years had bleeding complications. The overall incidence of bleeding complication in the hematology department was 0.56%. The bleeding was significantly minor (51.23%). Among this group, petechiae was the most common hemorrhage symptoms: 31.71%.The bleeding was major in 48.77%. In this group, the principal cause of the bleeding events was acute leukemia (n=13; 37.41%); that was the main likely cause of intracranial hemorrhage which accounted for 29.27%. Hemophilia was the second cause of bleeding episode (n=5; 14.29%) followed by bone marrow failure (n=4; 11.43%). The median platelet count was 39.92 (range 10 and 253) G/L.Conclusion: Bleeding event is rare and mostly associated with acute leukemia. The high proportion of intracranial hemorrhage in this group of pathology requests further studies on the outcome and predictive factors of it.Key words: bleeding complications, epidemiology, clinical characteristics, Congo